2019
DOI: 10.3126/njdrs.v16i0.31531
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Committees in Tensions? A Interpretive Case of Lalitpur Metropolitan City, Nepal

Abstract: The people of Nepal have witnessed several political/social transformations in the country, which have resulted in the restoration of peace, the promulgation of the new constitution. The restructuring of the country into 753 local units has led to the substantive devolution of the 22 power power/jurisdictions from the center to the local governments. In this scenario, the local governments implement their development plans through consumer committees by mobilizing the local beneficiaries. The purpose of this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The parents and who are sending their children in institutional schools and an institutional school head teacher are the unit of analysis. We have used the case study inquiry approach, "an empirical inquiry which investigates a contemporary phenomenon (the case) in depth and within its real-world context" (Yin, 2011, p. 16 as cited in Adhikari & Pasa, 2019). Also, case study research is used to study the contemporary issues by the application of more than one method to gather evidence like "direct observation of the events being studied and interviews of the persons involved in the event"(p. 12).…”
Section: Methodsmentioning
confidence: 99%
“…The parents and who are sending their children in institutional schools and an institutional school head teacher are the unit of analysis. We have used the case study inquiry approach, "an empirical inquiry which investigates a contemporary phenomenon (the case) in depth and within its real-world context" (Yin, 2011, p. 16 as cited in Adhikari & Pasa, 2019). Also, case study research is used to study the contemporary issues by the application of more than one method to gather evidence like "direct observation of the events being studied and interviews of the persons involved in the event"(p. 12).…”
Section: Methodsmentioning
confidence: 99%
“…The effective public service delivery demands strong and citizen responsive government, capable and neutral administrative system, active civil society, organized and capable consumer group and above all effective follow-up of standards practices. Adhikari and Pasa (2019) revealed that the chaos of bureaucratic hurdles to receive the development budgets from the Metropolitan of ice is demoralizing the community volunteers (consumer committee members) at local levels Adhikari and Pasa (2019). Local government should facilitate the fund releasing process to the consumer committees by easing the rules and regulations.…”
Section: Review Of Foundational Workmentioning
confidence: 99%